Association of Alanine Aminotransferase and Periodontitis: A Cross-Sectional Analysis—NHANES 2009–2012 - R. Constance Wiener; Usha Sambamoorthi; Richard J. Jurevic (International Journal of Inflammation)
Objective. Alanine Aminotransferase is an enzyme associated with not only liver diseases, liver conditions, and metabolic syndrome, but also inflammation. Periodontitis is associated with increased cytokines and other markers of inflammation. The purpose of this study is to determine if an independent association between Alanine Aminotransferase and periodontitis exists. Methods. Data from the 2009-2010 and 2011-2012 National Health and Nutrition Surveys (NHANES) were combined. Data concerning periodontitis and Alanine Aminotransferase were extracted and analyzed with Rao Scott Chi-square and logistic regressions. Serum Alanine Aminotransferase was dichotomized at 40 units/liter, and periodontitis was dichotomized to the presence or absence of periodontitis. Results. In bivariate Chi-square analyses, periodontitis and Alanine Aminotransferase were associated (p=0.0360) and remained significant in unadjusted logistic regression (OR = 1.30 [95% CI: 1.02, 1.65]). However, when other known risk factors of periodontitis were included in the analyses, the relationship attenuated and failed to reach significance (adjusted OR = 1.17 [95% CI: 0.85, 1.60]). Conclusion. Our study adds to the literature a positive but attenuated association of serum Alanine Aminotransferase with periodontitis which failed to reach significance when other known, strong risk factors of periodontitis were included in the analysis.